Smuggling the Renaissance : the illicit export of artworks out of Italy, 1861-1909 - Smalcerz, Joanna (Studies in the history of collecting & art markets, 2020)
"Smuggling the Renaissance: The Illicit Export of Artworks Out of Italy, 1861-1909 explores the phenomenon of art spoliation in Italy following Unification (1861), when the international demand for Italian Renaissance artworks was at an all-time high but effective art protection legislation had not yet been passed. Making use of rich archival material Joanna Smalcerz narrates the complex and often dramatic struggle between the lawmakers of the new Italian State, and international curators (e.g., Wilhelm Bode), collectors (e.g., Isabella Stewart Gardner) and dealers (e.g., Stefano Bardini) who continuously orchestrated illicit schemes to export abroad Italian masterpieces. At the heart of the intertwinement of the art trade, art scholarship and art protection policies the author exposes the socio-psychological dynamics of unlawful collecting"--